2010
DOI: 10.1038/nsmb.1763
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule FRET–derived model of the synaptotagmin 1–SNARE fusion complex

Abstract: Synchronous neurotransmission is triggered when Ca2+ binds to synaptotagmin 1, a synaptic vesicle protein that interacts with SNAREs and membranes. We used single-molecule FRET between synaptotagmin’s two C2 domains to determine that their conformation consists of multiple states with occasional transitions, consistent with domains in random relative motion. SNARE binding results in narrower intra-synaptotagmin FRET distributions and less frequent transitions between states. We obtained an experimentally deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
256
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(278 citation statements)
references
References 45 publications
22
256
0
Order By: Relevance
“…6) followed the expected r −6 dependence (where r is the distance between the corresponding methyl group and the probe) according to the known 3D structures of the domains (13,15,40). The observation of interdomain PBEs in multiple regions of the C 2 B domain for the N248C mutant and in multiple regions of the C 2 A domain for the V304C mutant is consistent with EPR (24), and single-molecule FRET (41,42) studies that revealed a dynamic relative orientation between the two domains. For the N248C mutant that contained the MTSL probe at the bottom of the C 2 A domain, we observed some strong PBEs (<0.4) and medium PBEs (= 0.4-0.6) for multiple cross-peaks at the bottom and middle of the C 2 B domain (Fig.…”
Section: Resultssupporting
confidence: 61%
“…6) followed the expected r −6 dependence (where r is the distance between the corresponding methyl group and the probe) according to the known 3D structures of the domains (13,15,40). The observation of interdomain PBEs in multiple regions of the C 2 B domain for the N248C mutant and in multiple regions of the C 2 A domain for the V304C mutant is consistent with EPR (24), and single-molecule FRET (41,42) studies that revealed a dynamic relative orientation between the two domains. For the N248C mutant that contained the MTSL probe at the bottom of the C 2 A domain, we observed some strong PBEs (<0.4) and medium PBEs (= 0.4-0.6) for multiple cross-peaks at the bottom and middle of the C 2 B domain (Fig.…”
Section: Resultssupporting
confidence: 61%
“…To obtain a distribution of fluorophore positions within an accessible volume, 100 independent simulated annealing dynamics runs were performed in the context of a fixed DNA duplex using CNS (45) as previously described (45,46). The average dye position was taken as the average position of the spiro atom (C24) in the lactam form of the dye and fixed rigidly to each of the sites in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…-independent binding of SYT to neuronal soluble N-ethylmaleimide-sensitive factor activating protein receptor on the plasma membrane (t-SNARE) [syntaxin/ synaptosomal-associated protein 25 (SNAP25)], most likely via its interaction with SNAP25 (17)(18)(19)(20)(21). This interaction is believed to position SYT on the prefusion SNARE complexes to trigger rapid exocytosis in response to Ca 2+ (20,22).…”
Section: +mentioning
confidence: 99%